The Upshot of Workspace and Work Spirit to the Employee Performance Enhancement in Jawa Timur Bank, Branch of Sumenep - Chamariyah, Chamariyah; Sujono, Sujono; Gs, Achmad Daengs (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
This research was conducted at Jatim Bank of Sumenep, with a total sample of 57 people. The objectives of this study are: 1) To find out how the description of the Workspace, work spirit, and employee performance in Jatim Bank, Sumenep Branch; 2) To test and analyze the influence of the Work space and work spirit on employee performance at Jatim Bank of Sumenep Branch; 3) To test nd analyze Work space, and work spirit simultaneously on employee performance at Bank Jatim, Sumenep Branch. Data analysis using SPSS. This type of research is explanatory research using a quantitative research approach. The results showed that: 1) Simultaneously, Work space , and Work Spirit have a significant influence on employee performance at Jatim Bank of Sumenep. So that in this case the hypothesis is accepted and its validity is proven; 2) Partially, the Workspace and Work Spirit have a significant influence on the employee performance of Jatim Bank of Sumenep. So that in this case the hypothesis is accepted and its validity is proven.